Global energy governance : the new rules of the game - Goldthau, Andreas; Witte, Jan Martin (Global Public Policy Institute ; Brookings Institution Press, 2010)
Analyzes the energy market from an institutionalist perspective and offers practical policy recommendations to deal with these challenges. This book presents perspectives on how regulatory institutions can ensure reliable sources of energy, evaluate financial risk, and provide emergency response mechanisms to deal with interruptions in supply.